Useful ultrasonographic parameters to predict difficult laryngoscopy and difficult tracheal intubation-a systematic review and meta-analysis - Gomes, Sara Cláudia Santos Hora (2021)
The Supplementary Material for this article can be found online at: https://www.frontiersin.org/articles/10.3389/fmed.2021.671658/full#supplementary-material